Folding and catalysis of the hairpin ribozyme. (1st June 2005) - Wilson, T.J.; Nahas, M.; Ha, T.; Lilley, D.M.J.
Abstract : The active form of the hairpin ribozyme is brought about by the interaction of two formally unpaired loops. In a natural molecule, these are present on two adjacent arms of a four-way junction. Although activity can be obtained in molecules lacking this junction, the junction is important in the promotion of the folded state of the ribozyme under physiological conditions, at a rate that is faster than the chemical reaction. Single-molecule fluorescence resonance energy transfer studies show that the junction introduces a discrete intermediate into the folding process, which repeatedly juxtaposes the two loops and thus promotes their docking. Using single-molecule enzymology, the cleavage and ligation rates have been measured directly. The pH dependence of the rates is consistent with a role for nucleobases acting in general acid–base catalysis.